2022
DOI: 10.1177/22808000221120329
|View full text |Cite
|
Sign up to set email alerts
|

Irreversibility process analysis for SiO2-MoS2/water-based flow over a rotating and stretching cylinder

Abstract: Entropy is the measure of the amount of energy in any physical system that is not accessible for the useful work, which causes a decrease in a system’s thermodynamic efficiency. The idea of entropy generation analysis plays a vital role in characterizing the evolution of thermal processes and minimizing the impending loss of available mechanical power in thermo-fluid systems from an analytical perspective. It has a wide range of applications in biological, information, and engineering systems, such as transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Hayat et al [8] explored three-dimensional MHD flow with viscous dissipation and joule heating. Using the bvp4c approach, which is a finite difference code that implements the three-stage Lobatto IIIa formula in MATLAB (Version 2018b), Khan et al [9] studied the steady SiO 2 -MoS 2 /water hybrid nanofluid flow induced by a rotating and stretching cylinder. They found that azimuthal and wall stress characteristics decrease with increasing values of Reynolds number, whereas heat and flow distributions increase as the volume percentage of solid particles increases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hayat et al [8] explored three-dimensional MHD flow with viscous dissipation and joule heating. Using the bvp4c approach, which is a finite difference code that implements the three-stage Lobatto IIIa formula in MATLAB (Version 2018b), Khan et al [9] studied the steady SiO 2 -MoS 2 /water hybrid nanofluid flow induced by a rotating and stretching cylinder. They found that azimuthal and wall stress characteristics decrease with increasing values of Reynolds number, whereas heat and flow distributions increase as the volume percentage of solid particles increases.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the rotational velocity of magnetic particles in the base fluid is different from the vortices in the flow domain. Considering the above assumptions and extending the work of [6,9,[32][33][34][35], the conservation of mass, momentum, and energy equations are expressed as: Considering the above assumptions and extending the work of [6,9,[32][33][34][35], the conservation of mass, momentum, and energy equations are expressed as:…”
mentioning
confidence: 99%
“…The paper concludes that using MWCNT nanofluids can reduce the thermodynamic irreversibility in heat transfer processes, leading to more efficient heat transfer. References [18] and [19] are particularly notable for their investigations of entropy generation in various thermal systems.…”
Section: Introductionmentioning
confidence: 99%
“…Two different forms of hybrid nanofluids were used in a flattened tube and compared in terms of their heat transmission abilities and degree of thermodynamic irreversibility by Huminic and Huminic [22]. The irreversibility process study for SiO 2 -/ MoS 2 water-based flow through a rotating and stretching cylinder was researched by Khan et al [23]. Further interesting studies regarding thermal analysis are given in [24] and [25].…”
Section: Introductionmentioning
confidence: 99%